To seduce a sinner - Hoyt, Elizabeth, 1970- (New York : Forever, 2008)
After years of loving the rakish Lord Vale from afar, Melisande Fleming finally gets the chance to prove her feelings for him when he is jilted on his wedding day and she boldly offers to marry him, but his dark nightmares of his military career in the colonies and a deadly betrayal from the past threaten to tear them apart.
ADVENTURE
1
Keywords: Aristocracy (Social class) -- Fiction; Love stories; Historical fiction